2017
DOI: 10.4314/rj.v1i2s.2d
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of land surface temperatures from landsat ETM+ images for Durban, South Africa

Abstract: Abstract-Population increase within urban environments especially in the developing countries, has posed a need to understand the urban climates. While the importance of urban climates cannot be overemphasized, acquiring knowledge about contributing factors to urban climates can be challenging.Measuring land surface temperatures is one of the ways to acquire such knowledge which could be an uphill task if done manually. However, satellite remote sensing data could be applied to spatially estimate such factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…These statistical values are quite significant, and they are in full agreement with outcomes from other researches (Abutaleb et al, 2014;Adeline et al, 2014;A Ngie et al, 2016).…”
Section: Relationship Between Ndvi and Lstsupporting
confidence: 92%
“…These statistical values are quite significant, and they are in full agreement with outcomes from other researches (Abutaleb et al, 2014;Adeline et al, 2014;A Ngie et al, 2016).…”
Section: Relationship Between Ndvi and Lstsupporting
confidence: 92%
“…The intensity of anthropogenic activities and urban development worldwide are related to changes in land cover and vegetation and have disrupted the balance of natural ecosystems (Ngie et al 2016, Meera et al 2015, Mushtaq, Asima 2016. Land cover, Land Surface Temperature (LST) and Vegetation Indices (VIs) are regarded as significant parameters for monitoring environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it's found that the relation between Spatial distribution of the LST and surface materials and land use/land cover types is good indicator to evaluate general ecosystem and environmental status. LST is estimated using different remote sensing data in many fields such as; forestry, vegetation, climate change hydrology, oceanography, urban heat island and climate [13] [14] [15], where the remote sensing has high techniques which evaluate and monitor environmental changes [1]. In this case, Landsat is used as one of the widely remote sensors used, Landsat 8 follow the Landsat series which provides thermal data [1] [16].…”
Section: Introductionmentioning
confidence: 99%